Strategy For Improving Employee Performance Of Sahabat Yatim Indonesia - Yunitasari, Yunitasari; Sutrisno, Sutrisno (IQTISHADUNA: Jurnal Ilmiah Ekonomi Kita, 2024)
This research aims to determine the improvement in the performance of Sahabat Yatim Indonesia (SYI) Yogyakarta Branch employees by increasing the amount of Zakat, Infaq, and Sadaqah (ZIS) received. This research is qualitative, with data sources in the form of primary and secondary data. The method used in collecting data was interviewing and looking at the financial reports held by the SYI Yogyakarta branch. There were seven interview informants, including branch heads and employees of the SYI Yogyakarta branch. The validity of the data was tested using the source triangulation method. This research uses data analysis techniques, such as data reduction, presentation, and conclusion. The results of this research find that the strategy to improve employee performance carried out by the SYI Yogyakarta branch has gone according to plan; this is realized through measurable implementation and supervision through monitoring and evaluation. The strategy to increase ZIS revenues has also been running well. The increase in ZIS proves that this is accepted every month. The theoretical implications of this research can be helpful as a reference for further research on a similar theme. The practical implication of this research is that the SYI Yogyakarta branch can maintain employee performance in increasing ZIS acquisition. The leadership of the SYI Yogyakarta branch can provide policies for distributing employee performance according to employee duties and functions so that employee performance can run better by the organizational structure of the SYI Yogyakarta branch.